2002
DOI: 10.1007/bf02703352
|View full text |Cite
|
Sign up to set email alerts
|

Shear waves in a fluid saturated elastic plate

Abstract: In the present context, we consider the propagation of shear waves in the transverse isotropic fluid saturated porous plate. The frequency spectrum for SH-modes in the plate has been studied. It is observed that the frequency of the propagation is damped due to the two-phase character of the porous medium. The dimensionless phase velocities of the shear waves have also been calculated and presented graphically. It is interesting to note that the frequency and phase velocity of shear waves in porous media diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These trends obey the elastic and thermoelastic properties of the solid. Figures [13][14][15][16][17][18] show the comparisons between temperature θ's, displacement component u's, v's, the force stress components σ xx 's, σ yy 's, and σ xy 's, for the cases of two different values of magnetic field and rotation (Ω = 0.2) under three theories.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These trends obey the elastic and thermoelastic properties of the solid. Figures [13][14][15][16][17][18] show the comparisons between temperature θ's, displacement component u's, v's, the force stress components σ xx 's, σ yy 's, and σ xy 's, for the cases of two different values of magnetic field and rotation (Ω = 0.2) under three theories.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The reflection and the transmission of plane SH wave through a self-reinforced elastic layer sandwiched between two homogeneous visco-elastic solid half-spaces have been studied by Chaudhary et al [11] Chattopadhyay and Chaudhary [12] studied the propagation of magnetoelastic shear waves in an infinite self-reinforced plate. Pradhan et al [13] studied the dispersion of Loves waves in a self-reinforced layer over an elastic nonhomogenous half-space. The propagations of plane waves in fibre-reinforced media were discussed by Chattopadhyay et al [14] Othman and Song [15] showed the effects of initial stress, thermoelastic parameter, and thermal boundary condition on the reflection amplitude ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of reflection of plane waves at the free surface of a fiber-reinforced elastic half-space was discussed by Singh and Singh [7]. Pradhan et al [8] studied the dispersion of Love waves in a self-reinforced layer over an elastic non-homogenous half-space. The propagation of plane waves in fiber-reinforced media was discussed by Chattopadhyay et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chattopadhyay et al discussed the effects of irregularity on the propagation of guided SH‐waves. SH‐waves in a fluid saturated elastic plate was observed by Pradhan et al . Chakraborty and Dey studied the propagation of Love waves in water‐saturated soil underlain by a heterogeneous elastic medium.…”
Section: Introductionmentioning
confidence: 99%